Knowledge and attitude regarding child abuse among primary health care physician in Abha, Saudi Arabia, 2018 - Safar A Alsaleem; Mohammed A Alsaleem; Ahmed M Asiri; Saif S Alkhidhran; Waleed S. S. Alqahtani; Mohammad S Alzahrani; Huda A Assiri; Khadejah M Alshahrany; Awad S Alsamghan (Journal of Family Medicine and Primary Care, 2019)
Backgrounds: Child abuse or child maltreatment is physical, sexual, or psychological maltreatment or neglect of a child or children, especially by a parent or other caregiver. Child abuse may include any act or failure to act by a parent or other caregiver that results in actual or potential harm to a child, and can occur in a child's home or in the organizations, schools, or communities the child interacts with. This study was conducted to assess the primary health care (PHC) centers' physicians' knowledge and attitude toward child abuse including its types, and child neglect with their behavior regarding reporting of abuse cases. Methods: A cross-sectional study was conducted in Abha which is the capital of Aseer Province, including all PHC physicians (about 475) working in PHC centers. Data regarding physicians' demographic characteristics, perception, and awareness regarding child abuse and neglect were collected by self-administrative questionnaire in the PHC center during their time between patients' consultation. Results: The study included 300 PHC physicians whose ages ranged from 25 to 50 years old with mean age of 28 years. About 65% of the physicians were males and 69% of them were married with about 73% having at least one child. Overall, 96.3% of the physicians recorded good awareness level regarding types of child abuse and 97.3% recorded good awareness level regarding child neglect patterns. Underreporting of child abuse cases was recorded by about 64% of physicians. Conclusion: Regarding child abuse and neglect, PHC physicians have good knowledge, optimal attitude, and positive perception. There was also the problem of underreporting of suspected child abuse cases among PHC physicians in Saudi Arabia, with many barriers to report, such as community traditions; unclear reporting strategy was identified.